Utilização da cinza da casca de arroz em cimentação de poços de petróleo - Soares, Lech Walesa Oliveira (2015)
Pozzolanic materials such as rice husk ash are widely used to substitute part of cement, because they react with calcium hydroxide (CH) producing calcium silicate hydrate (C-S-H), which aggregate better physical, chemical and mechanical properties to the cement slurry. The usage of rice husk biomass ash from agribusiness in addition to or partially replacing cement is a noble purpose and a good way of sustainable development which currently is an obsession around the world. The ashes utilized in this study were characterized by: scanning electron microscopy technique (SEM), Fourier transform infrared spectroscopy (FTIR), Energy-dispersive X-ray spectroscopy (EDX) and BET method. The pozzolanic activity of RHA and WRHA in cement slurries was evaluated by: thermal-gravimetric technique and derivative thermogravimetry (TGA/DTG), X-ray diffraction (XRD) and Compressive Strength. The slurries formulated with additions of 10% and 20% of RHA and WRHA were cured for 28 days at 58 °C. The results of thermal analysis demonstrated that a 20% WRHA addition caused a reduction of approximately 73% of Portlandite (calcium hydroxide – CH) phase related to standard slurry (STD). The XRD scans also demonstrated the reduction of the Portlandite peaks’ intensity for each slurry compared with STD slurry. The RHA and WRHA react chemically with Portlandite producing calcium silicate hydrate (C-S-H), confirming their effect as a pozzolanic agent. The WRHA presented the best results as a pozzolanic material.